Assessment of Knowledge Regarding Safety Profile, Use, and Boxed Warnings of Fluoroquinolones Among Healthcare Professionals in Saudi Arabia: A Potential Implication for Drug Regulatory Authorities - Mallhi, Tauqeer Hussain; Alanazi, Abdullah Salah; Khan, Yusra Habib; Alotaibi, Nasser Hadal; Salman, Muhammad; Alzarea, Abdulaziz Ibrahim; Khan, Salah-Ud-Din; Alruwaili, Nabil K.; Alenazi, Alaa Salah; Alatawi, Ahmed D.; Iqbal, Zafar; Butt, Muhammad Hammad; et al. (Frontiers in Medicine, 2022)
Background: Despite a series of “boxed warnings” (BW) issued by the FDA, fluoroquinolones (FQs) are among the most prescribed antibiotics across the globe. Moreover, few studies demonstrated that BW of FQs had little or no impact on prescribing patterns among healthcare professionals (HCPs), which might be attributed to the lack of knowledge towards such warnings. Since the FQs contribute a major proportion of antimicrobial prescriptions in Saudi Arabia (KSA), the current study was aimed to ascertain the extent of knowledge towards safety profile, use, and BW of FQs among HCPs working in KSA. Methods: This cross-sectional study (May–August 2021) was conducted among HCPs working in KSA through a validated questionnaire. The HCPs were requested to identify the indications, adverse effects (AEs), and BW of FQs. The knowledge score was estimated among participants and its association with demographics was ascertained through Chi-squared test, Student`s t-test or Mann-Whitney U and One-way ANOVA or Kruskal Wallis Test, where appropriate. Results: Of 573 participants (age: 36.1±10.6, males: 59.7%), 262 (45.8%) were prescribers reporting frequent use of ciprofloxacin, levofloxacin, and ofloxacin. One-fourth (25.6%) of the prescribers did not recognize nalidixic acid as an agent from FQs class. About 60% of participants correctly identified the mechanism of action of FQs. The average knowledge score was 14.8 ± 6.4, where only 21.5% respondents scored ≥50%. The average knowledge score for indications, AEs and BW domains were 5.29±3.05, 6.17±4.05 and 2.3±1.5, respectively. Only 75 (13.1%) participants recognized half of the BW and 38.6% identified at least one warning. The HCPs aged >40 years (p=0.043), non-Saudis (p<0.001), working in Riyadh and Eastern regions (p<0.001), pharmacy and medicine disciplines (p<0.001), practicing in public sectors (p=0.004), and having experience of >10 years (p<0.001) were significantly associated with high knowledge score. Conclusions: This study demonstrates the unsatisfactory knowledge towards usage, safety profile and BW of FQs among HCPs which may put patients at increased risks of AEs. The knowledge score differed among various socio-demographic groups. There is a dire need to initiate antimicrobial-focused educational campaigns among HCPs regardless of their specialties, and methods to improve education and disseminate FDA warnings in practice.